Analisis Keuntungan Usaha Pengolahan Nira Aren di Kelurahan Lowu Satu Kecamatan Ratahan Kabupaten Minahasa Tenggara - Yuristi Monika Rolos; Sherly Gladys Jocom; Barce Andries Feriano Wariki (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2026)
This study aims to analyze and compare the profitability of palm sugar and cap tikus businesses so that farmers can determine which type of business is more profitable and sustainable. This study was conducted in May-July 2025 using a quantitative descriptive method with primary and secondary data. The research sample consisted of 4 palm sugar respondents selected purposively from 24 active farmers, and 4 cap tikus respondents. The analysis was carried out by calculating production costs, revenues, and profits based on the same volume of palm sap raw material, namely 152.5 liters. The results showed that the production cost per liter in the palm sugar business was Rp. 349.37 with revenues of Rp. 3,569.21, resulting in a profit of Rp. 3,219.84. Meanwhile, the cap tikus business had a production cost of Rp. 364.16 per liter with revenues of Rp. 3,480 and a profit of Rp. 3,115.84. The difference in profit between the two businesses was relatively small, namely Rp. 104 per liter. This study concluded that both palm sap processing businesses were equally profitable for farmers with a slight difference in profits. This information is expected to help farmers in making business decisions based on economic considerations and also provide input for local governments in formulating policies for developing businesses based on palm sap commodities.